Taxonomic status of the black fly Prosimulium italicum Rivosecchi (Diptera: Simuliidae) based on genetic evidence - Kúdela, Matúš; Adler, Peter H.; Kúdelová, Tatiana (Zootaxa, 2018)
The black fly Prosimulium italicum Rivosecchi, distributed in the Apennines and Sicily, was described as a subspecies of Prosimulium hirtipes (Fries), based on a few morphological details. It subsequently was considered conspecific with P. hirtipes and the name was synonymized. Analyses of polytene chromosome banding patterns and sequences of mitochondrial DNA (COI and COII) revealed deep genetic divergence between P. italicum from Italy and P. hirtipes from northern and central Europe and confirmed the species status of P. italicum. Populations of P. italicum either lack chromosomal inversion IS-9 or carry it as an X-chromosome polymorphism, whereas all analyzed populations of P. hirtipes (Slovakia, Sweden, England, and Scotland) are fixed for IS-9. The average K2P genetic distance was 3.7% between P. italicum and P. hirtipes from northern Europe (Sweden) and 4.3 % between P. italicum and P. hirtipes from central Europe (Slovakia). Cytogenetic analysis showed the presence of two cytoforms of P. hirtipes (‘A’ in Sweden and Slovakia and ‘B’ in England and Scotland) and two cytoforms of P. italicum (‘A’ in Sicily and ‘B’ in Campania and Basilicata), all of which differ in their sex chromosomes and autosomal polymorphisms, suggesting that P. hirtipes and P. italicum might each be a complex of cryptic species.